Cytotoxic properties of phosphinegold (I) dithiocarbamates on breast carcinoma cell line MCF-7 - Goh, Zheng Jie (2017)
Statistical report by World Health Organization showed an increase of 20.5% in total number of cancer caused deaths from year 2000 to year 2011 with the total number of cancer caused deaths in year 2011 hitting 11.39% of the total number of deaths. Development of drug resistance of cancer and severe side effects of anti-cancer drug has been the reasons known to the increase in total number of cancer caused deaths. And this situation has call upon development of anticancer drug with better selectivity, enhanced therapeutic index, minimal side effects and is able to overcome the resistance phenomena. In this study, cytotoxic property of three phosphinegold(I) dithiocarbamates, R3PAu[S2CN(iPr)CH2CH2OH], for R = Ph (1), Cy (2) and Et (3) was studied against breast cancer cell line, MCF-7. Cell cytotoxicity was tested using methylthiazolyldiphenyl-tetrazolium bromide (MTT) cell viability assay, present of apoptosis was tested using apoptotic assay using acridine orange / propidium iodide (AO/PI) staining, further validation using DNA fragmentation test. Gene expression study employed human apoptosis PCR array analysis and protein detection was done by caspase activity assays. Based on MTT cell viability assay, cytotoxicity of 1, 2, and 3 against MCF-7 is confirmed with 1, 2, and 3 exhibiting greater cytotoxicity than commercial drug cisplatin. Besides that, acridine orange / propidium iodide (AO/PI) cell apoptotic assay and DNA fragmentation test showed that MCF-7 cells treated with 1, 2 and 3 underwent apoptosis, at the same time cells treated with 2 and 3 also underwent necrosis. On the other hand, human apoptosis PCR-array analysis on MCF-7 cells treated with 1, 2 and 3 exhibited up regulation of CASP7, CASP8, CASP9 and CASP10 outlining the evidence of apoptosis which has occured in MCF-7 cells treated with 1, 2 and 3. The result is further supported by detection of caspases activities of caspase-7, caspase-8, caspase-9 and caspase-10. Induction of both intrinsic and extrinsic apoptosis by 1, 2 and 3 were demonstrated in the human apoptosis PCR-array analysis and the detection of caspases activities of caspase-7, caspase-8, caspase-9 and caspase-10 detection. Result of human apoptosis PCR-array analysis on MCF-7 also suggested that compound 1 has activated TP53 gene, has compound 2 activated only the TP73 gene, whereas compound 3 has activated both the TP53 and TP73 genes. The mechanism of death induced by compound 1 is apoptosis while compound 2 and compound 3 induced both apoptosis and necrosis.